Lontar Usada Cukildaki: Kajian Teologi dan Pendidikan Kesehatan Pada Masyarakat Hindu di Bali - Asthadi Mahendra Bhandesa; I Putu Gede Sutrisna; I Putu Agus Endra Susanta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The Usada Cukildaki is one of the traditional medicine texts in Bali contained in the form of lontar.It contains the knowledge of health problems and their treatment. The purpose of this research wasto analyze the theological value and health education held in the Lontar of Usada Cukildaki andits role for the Hindu community in Bali. The method used in this research was descriptivequalitative. The first step was to analyze the theological value and health education through acontent analysis approach, then to find out its role for the Hindu community in Bali, and it is carriedout using a grounded theory approach. The results indicated that in the Lontar of Usada Cukildakithere were theological aspects in the form of worshiping Sang Hyang Tunggal, Sanghyang TriMurti (Brahma, Vishnu, Iswara), Dewata Nawa Sangga, Sang Hyang Kamulan, Sang HyangDurga, Sang Hyang Aji Saraswati, and Ida Bhatara Sri, and based on the concept of ShivaSidhanta in the form of worshiping Bhatara Iswara, Bhatara Mahadewa, Bhatara Vishnu, Shiva,Sada Shiva and Parama Shiva including worshiping Sang Hyang Kala Cakra, Sang Hyang TayaTayi, Sang Hyang Sangenge, Sang Hyang Bayu, Sang Hyang Hyang Surya Candra, Sang HyangBhatara Samara, and Sang Hyang Kresna Murti. The value of health education given by SangHyang Cukildaki is in the form of knowledge of various types of diseases, characteristics ofdiseases and medicinal ingredients and how to use them in the context of the protection and healingprocess from all kinds of existing diseases. It includes performing a Caru ceremony to harmonizethe universe and its contents. Lontar Usada Cukildaki for the Hindu community in Bali is utilizingmedicinal materials and plants that have medicinal properties and properties to improve the healingprocess, especially in increasing the body's immunity and health problems. The materials includegarlic, coriander, turmeric, ginger, coconut oil, honey, white turi tree bark, candlenut tree bark,kara lingsir peanut leaves, kemeniran, dadap, dewa leaves, reed starfruit, cangkem butuh root,white jarak and so on. In conclusion, Usada Cukildaki is a traditional medicine text with theconcept of Hindu Theology with the Local Genius perspective for the Hindu community in Bali